Strategi Komunikasi Organisasi Dalam Optimalisasi Komunikasi Interpersonal Karyawan PT Bina Cipta Indokarya Di Kota Batam - Melati Suci; Riswandi Riswandi (LPPM Universitas Putera Batam, 2025)
The training services industry in Indonesia, especially in the city of Batam, is growing rapidly. PT Bina Cipta Indokarya is a K3 training service company that has only been established for less than five years. However, in the midst of this young company's journey, a significant challenge arose, especially in terms of internal communication among its employees. PT Bina Cipta Indokarya faces challenges in maintaining smooth interpersonal communication between employees. This is crucial because ineffective communication can directly affect productivity and coordination between employees. The purpose of this study is to look at organizational communication strategies that can improve interpersonal communication at PT Bina Cipta Indokarya. The method used is qualitative, using a descriptive approach based on Snowball Sampling. Data was collected through in-depth interviews and participant observation. The results showed that the company uses four communication approaches: (1) direct communication between superiors and subordinates (simple control), (2) use of communication technology (technical control), (3) structure of formal procedures (bureaucratic control), and (4) development of a mutually supportive communication culture (concertive control). This study confirms the importance of openness, empathy, and emotional support in corporate culture for improving the effectiveness of interpersonal communication.